2017
DOI: 10.1111/pbi.12827
|View full text |Cite
|
Sign up to set email alerts
|

OsASR2 regulates the expression of a defence‐related gene, Os2H16, by targeting the GT‐1 cis‐element

Abstract: SummaryThe GT‐1 cis‐element widely exists in many plant gene promoters. However, the molecular mechanism that underlies the response of the GT‐1 cis‐element to abiotic and biotic stresses remains elusive in rice. We previously isolated a rice short‐chain peptide‐encoding gene, Os2H16, and demonstrated that it plays important roles in both disease resistance and drought tolerance. Here, we conducted a promoter assay of Os2H16 and identified GT‐1 as an important cis‐element that mediates Os2H16 expression in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 72 publications
1
57
0
Order By: Relevance
“…Water loss assay was performed with 10 potato plants for each treatment as described previously (Li et al , ). About 30 leaves of potato plants treated with CuSO 4 or MgSO 4 were harvested.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water loss assay was performed with 10 potato plants for each treatment as described previously (Li et al , ). About 30 leaves of potato plants treated with CuSO 4 or MgSO 4 were harvested.…”
Section: Methodsmentioning
confidence: 99%
“…The cross‐linking reaction was stopped by adding glycine to a final concentration of 0.125 M and applying a vacuum for an additional 5 min. Subsequently, the chromatin was isolated and sonicated as described previously (Li et al , ). Anti‐FLAG monoclonal antibody (Abways) and Co‐immunoprecipitation Kit (Thermo) were used for immunoprecipitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidences showed that ASR proteins play important roles in plant growth and fruit ripening [1,[25][26][27], as well as in regulation of floral development and flowering time [15,28,29]. The ASR proteins have been well documented for their responses to multiple abiotic stresses, including drought, salt, heat, cold, and exposure to cadmium (Cd) and aluminum (Al) [9,24,[30][31][32][33][34][35][36][37][38].…”
mentioning
confidence: 99%
“…Several previously reported genes that contribute resistance to ShB, such as OsACS2 (11), 14-3-3GF14f (35), OsPAL4 (36), OsPR4b (37), OsMYB4 (38), and OsASR2 (39), are present in our DEGs dataset. These results confirmed the effectiveness of our RNA-Seq experiment.…”
Section: Discussionmentioning
confidence: 75%